1990
DOI: 10.1177/002224299005400102
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Evaluations of Brand Extensions

Abstract: Two studies were conducted to obtain insights on how consumers form attitudes toward brand extensions, (i.e., use of an established brand name to enter a new product category). In one study, reactions to 20 brand extension concepts involving six well-known brand names were examined. Attitude toward the extension was higher when (1) there was both a perception of “fit” between the two product classes along one of three dimensions and a perception of high quality for the original brand or (2) the extension was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

74
1,765
7
63

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,508 publications
(1,909 citation statements)
references
References 31 publications
74
1,765
7
63
Order By: Relevance
“…The measures of company trustworthiness and expertise in a CBA context use four bipolar adjectives adapted from the scale developed by Newell and Goldsmith (2001) to assess corporate credibility (two items per dimension). Functional fit and image fit employ the methodology followed by Lafferty et al (2004) and a six-item, seven-point bipolar scale with pairs of adjectives from Aaker and Keller (1990), Till and Busler (2000), Rifon et al (2004), andBecker-Olsen et al (2006). The measure of CSR image uses a sixitem, seven-point Likert scale that consists of items from studies by Menon and Kahn (2003), Dean (2002), and Lichtenstein et al (2004).…”
Section: Methodsmentioning
confidence: 99%
“…The measures of company trustworthiness and expertise in a CBA context use four bipolar adjectives adapted from the scale developed by Newell and Goldsmith (2001) to assess corporate credibility (two items per dimension). Functional fit and image fit employ the methodology followed by Lafferty et al (2004) and a six-item, seven-point bipolar scale with pairs of adjectives from Aaker and Keller (1990), Till and Busler (2000), Rifon et al (2004), andBecker-Olsen et al (2006). The measure of CSR image uses a sixitem, seven-point Likert scale that consists of items from studies by Menon and Kahn (2003), Dean (2002), and Lichtenstein et al (2004).…”
Section: Methodsmentioning
confidence: 99%
“…This concept has been maturely studied in brand extension (e.g., Aaker and Keller 1990) and celebrity endorsement (e.g., Kamins and Gupta 1994), while the research is still not perfect in the aspect of CSR in spite of the existing concern by some scholars (Nan and Heo 2007). There has not been a consistent conclusion about the moderating role of fit in CSR implementation effects, which means that scholars who support positive moderating effect (Sen and Bhattacharya 2001;Menon and Kahn 2003), negative moderating effect (Forehand and Grier 2003), or no significant effect (Lafferty 2007(Lafferty , 2009Hoek and Gendall 2008) exist.…”
Section: The Moderating Role Of Fitmentioning
confidence: 99%
“…In the consumption context, research on the evaluation of brand extensions has generally found that parent brand associationsÕ influence on customersÕ evaluations of new products is stronger when customers perceive a high fit between the product and the brand (e.g., Aaker and Keller, 1990;Smith and Park, 1992). Perceived fit refers to the similarity between the existing brand and the new product or service.…”
Section: Corporate Identity Attractiveness For Consumers 249mentioning
confidence: 99%